Mechanical and fracture toughness behavior of TPNR nanocomposites - Ahmad, S. H.; Rasid, Rozaidi; Surip, S. N.; Anuar, Hazleen; Czigany, T.; Abdul Razak, S. B. (SAGE Publications, Inc, 2007)
Thermoplastic natural rubber (TPNR) nanocomposites containing organophilic layered silicates were prepared by melt blending method at 180 C using internal mixer (Haake 600P). The aim of this study is to determine the influence of the organoclay filler on the mechanical and fracture properties. In this study, two mixing methods were employed to incorporate filler into matrix, namely the direct (DM) and indirect (IDM) method. The mechanical properties of TPNR nanocomposites were studied using tensile, flexural, and impact tests. The tensile and flexural tests revealed that the optimum loading of organoclay was at 4 wt% using the indirect method of mixing. Plane stress fracture toughness of thermoplastic natural rubber (TPNR) nanocomposite was determined by the essential work of fracture (EWF) concept using tensile-loaded deeply double-edge notched (DDEN-T) specimens. The EWF measurements indicated that the specific essential work of fracture (we ) decreased in the presence of nanoclay. Nevertheless, these TPNR nanocomposites met the basic requirement of the EWF concept of full ligament yielding, which was marked by a load drop in the force–displacement curves of the DDEN-T specimens.